2017
DOI: 10.1080/1061186x.2017.1390671
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of chloroquine phosphate loaded nanostructured lipid carriers using Box–Behnken design and its antimalarial efficacy

Abstract: Chloroquine was once the most widely used antimalarial for nearly eight decades for its safety, efficiency, stability, low cost and finally for its less toxic nature. But its use and efficacy got slowly decreased with the increase of chloroquine resistant strains of Plasmodium species throughout the world. Lipid based nanodrug delivery systems have been very popular in the recent times as they are very less toxic, have drug targeting capabilities and also reduces the dosing frequency by increasing efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…In 1944, scientists modified the structure of chloroquine by adding a hydroxyl group to it, and developed a new antimalarial drug, hydroxychloroquine, which was less toxic and more effective against malaria. 5 At present, two independent experiment teams from China have confirmed that chloroquine has an impact against the SARS virus in vitro. 6 At present, the safety of chloroquine phosphate in the treatment of elderly patients with COVID-19 cannot be determined, but the rate of critical illness in the elderly is high and chloroquine phosphate can still be used as an alternative antiviral drug for the elderly.…”
Section: Republic Of China and The National Administration Of Traditimentioning
confidence: 94%
“…In 1944, scientists modified the structure of chloroquine by adding a hydroxyl group to it, and developed a new antimalarial drug, hydroxychloroquine, which was less toxic and more effective against malaria. 5 At present, two independent experiment teams from China have confirmed that chloroquine has an impact against the SARS virus in vitro. 6 At present, the safety of chloroquine phosphate in the treatment of elderly patients with COVID-19 cannot be determined, but the rate of critical illness in the elderly is high and chloroquine phosphate can still be used as an alternative antiviral drug for the elderly.…”
Section: Republic Of China and The National Administration Of Traditimentioning
confidence: 94%
“…The mixture was centrifuged at 15,000 rpm for 30 min at 25 ± 0.5 • C by a centrifuge (model 2-16P, Sigma, Osterode am Harz, Germany) to separate the lipid. The resultant supernatant (aqueous phase) was diluted in order to quantify the amount of AT using a UV spectrophotometer (Tokyo, Japan) [21] The partition coefficient (Log P) was then calculated using the following equation [22]: PC = log Added drug content − Drug content in aqueous phase Drug content in aqueous phase (1)…”
Section: Preliminary Study 221 Partitioning Behavior Of At In Solid Lipidsmentioning
confidence: 99%
“…Samples were transferred from the shaker to a centrifugation machine and centrifuged at 15,000 rpm for 30 min. To filter the supernatant, a 0.22 µm membrane filter (HiMedia, Mumbai, India) was used [21]. The filtered supernatant was assayed by a UV spectrophotometer.…”
Section: Equilibrium Solubility Of At In Different Oilsmentioning
confidence: 99%
“…Dessa forma, é imprescindível e impreterível a criação de novas estratégias de tratamento para a malária. Nesse contexto, como o processo de pesquisa e desenvolvimento de drogas demanda um tempo considerável, a reformulação dos antimaláricos disponíveis, por meio do uso de novos sistemas de delivery, pode ser considerada uma solução viável e menos dispendiosa de tempo e recursos (Baruah et al, 2018;Medhi et al, 2018;Rajendran et al, 2017).…”
Section: Sistema De Liberação Modificada Para O Tratamento Da Maláriaunclassified